An overview of trends in geographical publication at Stellenbosch University. Issue 3 (1st September 2020) - Spocter, Manfred; Visser, Gustav; de Waal, Jan Hofmeyr
ABSTRACT: The Department of Geography and Environmental Studies at Stellenbosch University is the oldest geography department in South Africa and celebrates its centenary in 2020. This paper provides insight into a range of publications that emanated from the department during that time. The presentation is periodized in three sections of review and analysis: the genesis of the department from 1920 up to 1947; the apartheid period of 1948 to 1993; and the democratic era (1994–2019). Drawing on various sources it appears that published research in the department amounted to a meagre output in the early years by one staff member. Publication numbers grew in the 1960s and 1970s. This period was, however, characterized by publications mostly in South African journals and generally in Afrikaans. This period also consolidated a positivist epistemology that remains to the present. Research output increased in the 1990s. The past decade (2010s) saw publication output rise steeply to register more than half of all publications ever produced in the department. This was due to the establishment of research centres in the department, increased staff complements and the appointment of research fellows.